2017
DOI: 10.1038/srep46208
|View full text |Cite
|
Sign up to set email alerts
|

Tomatidine enhances lifespan and healthspan in C. elegans through mitophagy induction via the SKN-1/Nrf2 pathway

Abstract: Aging is a major international concern that brings formidable socioeconomic and healthcare challenges. Small molecules capable of improving the health of older individuals are being explored. Small molecules that enhance cellular stress resistance are a promising avenue to alleviate declines seen in human aging. Tomatidine, a natural compound abundant in unripe tomatoes, inhibits age-related skeletal muscle atrophy in mice. Here we show that tomatidine extends lifespan and healthspan in C. elegans, an animal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
101
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 65 publications
(125 reference statements)
4
101
0
Order By: Relevance
“…To visualize the mitochondrial networking in the C. elegans body wall muscle tissue, csa-1, csb-1 , and csa-1;csb-1 mutants were crossed to a myo3::gfp reporter strain (N2 background). Images were acquired with a Zeiss confocal microscopy and analyzed as described previously [53]. Worms were transferred to drug-treated plates from the late L4 stages until Day 7 unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To visualize the mitochondrial networking in the C. elegans body wall muscle tissue, csa-1, csb-1 , and csa-1;csb-1 mutants were crossed to a myo3::gfp reporter strain (N2 background). Images were acquired with a Zeiss confocal microscopy and analyzed as described previously [53]. Worms were transferred to drug-treated plates from the late L4 stages until Day 7 unless otherwise noted.…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial networking was assessed using an arbitrary scale from 1-5. Healthy, organized mitochondrial networks in which the mitochondria are longer, less circular, aligned with the muscle fibers, and with reduced interconnecting mitochondrial strings received a score of 5 [53]. The mitochondrial networking score was reduced if the mitochondria appeared disorganized and more circular with mitochondria forming a network of irregular shapes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, tomatidine, a natural compound abundant in unripe tomatoes, inhibits age-related skeletal muscle atrophy in mice and extends health-and lifespan in C. elegans. Mechanistic analysis showed that tomatidine stimulates mitochondrial biogenesis and PINK1-and DCT1related mitophagy and increases healthspan (Fang et al, 2017). Moreover, dct-1, pink-1, and pdr-1 are engaged in lifespan extension induced by mild mitochondrial stress achieved by frataxin depletion-induced iron-starvation in C. elegans (Schiavi et al, 2015).…”
Section: The Role Of Mitophagy In Agingmentioning
confidence: 99%
“…In fact, dct-1 is transcriptionally induced under the control of skn-1 and daf-16 [the nematode homolog of mammalian nuclear factor, erythroid 2 like 2 (NFE2L2, better known as NRF2) and forkhead box O3 (FOXO3), respectively] to remove dysfunctional mitochondria via mitophagy and coordinate mitochondrial biogenesis and mitophagy . Mitochondrial biogenesis and mitophagy may cooperate to antagonize the aging process Fang et al, 2017). Interestingly, tomatidine, a natural compound abundant in unripe tomatoes, inhibits age-related skeletal muscle atrophy in mice and extends health-and lifespan in C. elegans.…”
Section: The Role Of Mitophagy In Agingmentioning
confidence: 99%